The role of core strength in front crawl performance: a qualitative analysis of expert coaches` perspectives - Dai, J.; Xu, J.; Dai, Z. (Frontiers in Sports and Active Living, 2026)
While core strength is theorized to be crucial for swimming performance, empirical evidence remains conflicting, and the perspectives of high-performance coaches—key stakeholders in training prescription-are largely unexplored. This qualitative study examined the perceptions of eight expert Chinese swimming coaches (seven males, one female) regarding the role of core strength in front crawl performance and explored how and why they prescribe core-specific training. Semi-structured interviews were conducted, transcribed verbatim, and analyzed using thematic analysis. Results revealed three central themes. First, all coaches unanimously affirmed core strength's importance through dual mechanisms: direct (force transmission, rotational power) and indirect (stabilization, drag reduction). Second, despite this consensus, assessment and training methods relied primarily on experiential knowledge rather than evidence-based protocols. Third, a "threshold effect" was identified, wherein coaches' experiential knowledge suggested that core training benefits may be most apparent in athletes with initial deficiencies. Based on these findings, we propose a conceptual model positing that core function operates through direct and indirect pathways, moderated by baseline capacity and transfer effectiveness. The model provides a testable framework to guide future research on how, when, and for whom core training is most effective, underscoring the need for swimming-specific diagnostic tools and integrated training protocols.